2017
DOI: 10.3390/nu9060620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Virtual Touch Quantification in Acoustic Radiation Force Impulse for Skeletal Muscle Mass Loss in Chronic Liver Diseases

Abstract: Background and aims: We sought to clarify the relationship between virtual touch quantification (VTQ) in acoustic radiation force impulse and skeletal muscle mass as assessed by bio-electronic impedance analysis in patients with chronic liver diseases (CLDs, n = 468, 222 males and 246 females, median age = 62 years). Patients and methods: Decreased skeletal muscle index (D-SMI) was defined as skeletal muscle index (SMI) <7.0 kg/m2 for males and as SMI <5.7 kg/m2 for females, according to the recommendations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The results of the study by Imai et al overall confirmed that sarcopenia negatively impacts the survival of patients with HCC, and is a valuable prognostic factor that might be impacted by liver functional reserve and the clinical stage of HCC. Therelationship between the loss of SMM, as assessed by bioelectric impedance analysis (BIA), and liver fibrosis, as measured by virtual-touch-quantification (VTQ) and acoustic-radiation-force-impulse elastography in patients with chronic liver disease (CLD), was reported by Nishikawa et al [ 2 ]. Interestingly, BCAAs-to-tyrosine ratio (BTR) showed the second strongest correlation with the VTQ level, and was an independent predictor for decreased SMM index.…”
Section: Skeletal Muscle Massmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the study by Imai et al overall confirmed that sarcopenia negatively impacts the survival of patients with HCC, and is a valuable prognostic factor that might be impacted by liver functional reserve and the clinical stage of HCC. Therelationship between the loss of SMM, as assessed by bioelectric impedance analysis (BIA), and liver fibrosis, as measured by virtual-touch-quantification (VTQ) and acoustic-radiation-force-impulse elastography in patients with chronic liver disease (CLD), was reported by Nishikawa et al [ 2 ]. Interestingly, BCAAs-to-tyrosine ratio (BTR) showed the second strongest correlation with the VTQ level, and was an independent predictor for decreased SMM index.…”
Section: Skeletal Muscle Massmentioning
confidence: 99%
“…The study by Imai et al [ 1 ] was based on imaging techniques, and, although these assessments are objective and not affected by defects in hepatic synthesis or retention of NaCl and water, they are either expensive or involve radiation and cannot easily be repeated to monitor progress. The other twostudies [ 2 , 3 ] that used BIA, which is based on a two-component model of body composition (fat and fat-free mass), may have drawbacks. As recently emphasized by Amodio et al [ 4 ] the validity of this technique is in fact critically dependent on assumptions relating to tissue density and hydration.…”
Section: Skeletal Muscle Massmentioning
confidence: 99%
See 1 more Smart Citation